The Meritocratic Illusion: Inequality and the Cognitive Basis of Redistribution - Arthur Blouin; Anandi Mani; Sharun Mukand; Daniel Sgroi (Institute of Labor Economics (IZA), 2024)
Can inequality in rewards result in an erosion in broad-based support for meritocratic norms? We hypothesize that unequal rewards between the successful and the rest, drives a cognitive gap in their meritocratic beliefs, and hence their social preferences for redistribution. Two separate experiments (one in the UK and the other in the USA) show that the elite develop and maintain "meritocratic bias" in the redistributive taxes they propose, even when not applied to their own income: lower taxes on the rich and fewer transfers to the poor, including those who failed despite high effort. These social preferences at least partially reflect a selfserving meritocratic illusion that their own high income was deserved. A Wason Card task confirms that individuals maintain their illusion of being meritocratic, by not expending cognitive effort to process information that may undermine their self-image even when incentivized to do otherwise.
Keywords: D91; C92; D63; D82; 330; inequality; meritocracy; redistribution; populism; motivated reasoning; social preferences